Discriminating factors of first-time and repeat visitors to wine festivals - Shanka, Tekle; Taylor, Ruth (Routledge, 2004)
While many events individually claim varied successes, it is worth acknowledging the growing competition between events and festivals in attracting and retaining repeat visitors. In particular, it is of interest to investigate festivals which have established a 'following' of visitors, and to establish what could sustain their attendees' interest for staging of future festivals. Event managers should be aware of the festival attributes that differentiate between two distinct visitor groups - the first-time visitor group versus the repeat visitors attending an annual festival on a regular basis. This paper investigates the attributes associated with the successful staging of a wine festival staged over a five-weekend period during the autumn of 2002 to determine which of the attributes significantly discriminate between first-time and repeat visitor groups. Results identified two attributes and four visitor characteristics that showed discriminating ability. The two festival attributes with discriminating abilities between the first-time visitors and repeat visitors were parking and services, while the four visitor characteristics that showed discriminating effects were age, place of residence, group composition, and information sources utilised. Results are discussed and implications for the festival organisers are proposed. © 2004 T. Shanka and R. Taylor.